Rupture of the lacrimal saccus of occuli sinistra with rupture of the palpebra occuli sinistra - Teresia, Vira; Nila Juwita, Oktarina (Institute of Computer Science (IOCS), 2023)
This research aims to analyze the case of rupture of lacrimal sac occuli sinistra with rupture of the palpebra occuli sinitra. The research method used qualitative with a case study approach. Data collection was carried out using primary and secondary methods. Primary was carried out through direct observation, while secondary data was obtained through journal literature and books. Case illustration: a 58 years old woman complained of pain in her left eye ± 1 day ago due to a traffic accident, that was a motorbike collision accompanied by lacerations and bleeding in the lower eyelid near the nose. Physical examination revealed that the patient appeared moderately ill, composmentis, GCS 15, blood pressure: 160/90 mmHg, pulse frequency: 70x/minute, respiratory frequency: 20x/minute, temperature: 36,80 C, and BMI: 23,4 kg/m2 is overweight. Physical examination of the eyes superior and inferior eyelids have edema (+), tenderness (+). In the lacrimal punctum, there was a tear in the vertical direction measuring ± 1.5 cm and bleeding. The palpebral fissure is the horizontal size = 30 mm and the vertical = 7 mm. The patient's treatment was planned to involve recanalization of the lacrimal sac occuli sinitra accompanied by palpebral hecting under general anesthesia. The 0.5% optiflox (levofloxacin 1 mg) eye drops were administered 1 drop/hour OS, methylprednisolone 3 x 4 mg tablets PO, levofloxacin 1 x 500 mg tablet PO, and amlodipine 1 x 10 mg tablet. This case report shows that rupture of lacrimal sac occuli sinistra and rupture of the palpebra occuli sinitra occurred due to indirect blunt trauma. Complications can be prevented by carrying out appropriate management and control of risk factors.